Biocontrol action of Trichothecium roseum against the wheat powdery mildew fungus Blumeria graminis f. sp. tritici - Zhu, Mo; Duan, Xiao; Cai, Pengkun; Zhang, Wanwan; Liu, Yan; Cui, Jiangkuan; Li, Zhengnan; Qiu, Zongbo (Frontiers in Sustainable Food Systems, 2022)
Trichothecium roseum is known to be a mycoparasite and inhibit phytopathogenic fungi. However, so far, only scarce information is available on the impacts of T. roseum on powdery mildews. Based on the morphological and molecular analysis, we identified T. roseum as a mycoparasite on colonies of the wheat powdery mildew fungus (Blumeria graminis f. sp. tritici, Bgt, recently clarified as B. graminis s. str.) and then showed that T. roseum was capable of efficiently impairing colony formation and conidial distribution of Bgt. After inoculation of T. roseum conidia on Bgt colonies, the biomasses of Bgt significantly decreased 1.46, 1.64, 7.55, and 10.49 times at 2, 4, 6, and 8 dpi, respectively. Thus, T. roseum, acting as a potential biological agent, impeded the developments of Bgt, making it a viable alternative for wheat powdery mildew control. Utilizing the Agrobacterium tumefaciens-mediated transformation (ATMT) system, a T. roseum strain that constitutively expressed green fluorescent protein was produced to improve the visualization of the T. roseum-Bgt interaction and showed direct hyphae interaction of T. roseum with Bgt structures during parasitic processes. These findings indicate that ATMT is a potent and efficient method for transforming T. roseum. Nevertheless, our results suggest that T. roseum is an antagonistic parasite of the wheat powdery mildew fungus, and hence, can be considered for phytopathogen management.